To fight or not to fight? An analysis of submission, struggle, and the design of contests - Achim Körber; Martin Kolmar (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1996)
This paper considers the players' behaviour in an asymmetric two-player contest. When do they decide to "struggle" and when to "subjugate"? Analysing contest-success functions it is found that two crucial prerequisites for "struggle" or "war" have to be met. Thus, such an equilibrium is possible but restrictive. If a self-interested rule-setter chooses the contest-success function endogenously we show that one player will always subjugate. Applications to rent-seeking and environmental regulation are discussed.
Keywords: D72; D78; L12; 330; Lobbying; Contest